Asymptotically exact theory of fiber-reinforced composite beams. (15th July 2020) - Le, K.C.; Tran, T.M.
Abstract: An asymptotic analysis of the energy functional of a fiber-reinforced composite beam with a periodic microstructure in its cross section is performed. From this analysis the asymptotically exact energy as well as the 1-D beam theory of first order is derived. The effective stiffnesses of the beam are calculated in the most general case from the numerical solution of the cell and homogenized cross-sectional problems.